Development of an Electronic Encyclopedia of Spermatophyta Sub Materials Based on Flipbook Maker for Class X High School Students - Yunita, Silvia; Wulandari, Sri; Suzanti, Fitra (FKIP - Universitas Riau, 2022)
The type of this research is research and development using the ADDIE Instructional Model which consists of the design phase, doing product design, validation sheets and limited test responses. Development, conducting product development and testing product validity from material experts, media experts and biology teachers. Implementation, conducted a limited trial of phase I on 10 students and phase II on 31 students of class XI MIPA. Evaluation, Conducting an evaluation of each stage carried out. The results of the analysis phase of the curriculum used in the learning process in schools is the 2013 curriculum. The basic competencies that are appropriate in the development of this Electronic Encyclopedia are KD (3.7) Plantae. The results of the analysis of the characteristics of students are known, students prefer to learn by discussion, students prefer to learn in an environment outside the classroom and are more interested in learning with books that have lots of pictures, so that the Flipbook Maker-based Encyclopedia of Spermatophyta learning resources was developed. Based on the results of the validity test and limited trial, the overall value of the category is very good so that it produces a quality Flipbook Maker-based Electronic Encyclopedia of Spermatophyta, which can be used as a learning resource.